Victorian Rainbow Makers: Variations on Colour Poetics - Charlotte Ribeyrol (Angles)
In his 1993 book retracing the history of synthetic dyestuffs, Anthony S. Travis describes the 19th century chemists who devised new aniline dyes for the expanding textile industry as “rainbow makers”. By conflating the materiality of coloured textiles and the prismatic hues of the sacred bow, Travis may have been trying to vindicate a scientific entreprise which many late 19th century artists and writers had shunned, echoing John Keats’s denunciation of the “unweaving” of the rainbow by modern science. This article explores the poetic instability generated by the 19th century colour revolution in the works of John Ruskin, William Morris, Walter Pater and Oscar Wilde so as to shed light on the complex reception of modern artificial colouring practices as opposed to the Homeric colour-sense.